Menguji Peran Mediasi Motivasi pada Pengaruh Konflik Interpersonal dan Beban Kerja terhadap Kinerja Karyawan PT Lung Cheong Brothers Industrial - Nafiudin; Andari; Yulinda (Universitas Serang Raya, 2023)
This study aims to determine the effect of interpersonal conflict and workload on employee performance mediated by work motivation at PT Lung Cheong Brothers Industrial. The method used is descriptive quantitative method The sample in this study amounted to 100 respondents and the analysis used is instrument test, classical assumption test, coefficient of determination, hypothesis test, path analysis and Sobel test using SPSS V25 for windows. The results of this study can be concluded that Interpersonal Conflict has a positive and significant effect on work motivation , workload has a positive and significant effect on work motivation , interpersonal conflict has a positive and significant effect on employee performance, workload has a positive and significant effect on employee performance, work motivation has a positive effect and significant on employee performance, with the Sobel test work motivation can mediate the relationship between interpersonal conflicts on employee performance, with the Sobel test work motivation can mediate the relationship between workload and employee performance